Inovasi Pengelolaan Pembelajaran Pendidikan Agama Islam Di SD Islam Baitul A’la Lubuk Linggau - Jon Berli; Nur Sasongko, Rambat; Danim, Sudarwan (UNIVERSITAS BENGKULU, 2025)
The objectives of this research are 1) Describe innovations in PAI learning planning in the implementation of PAI learning at Baitul A'la Islamic Elementary School, Lubuklinggau. 2) Describe the Implementation of PAI Learning Innovations in the Implementation of the Independent Curriculum at Baitul A'la Islamic Elementary School, Lubuklinggau; 3) Describe student learning outcomes regarding PAI learning innovations in the implementation of the Independent Curriculum at Baitul A'la Islamic Elementary School, Lubuklinggau. This research method is a qualitative descriptive study. Data collection techniques use interviews, observation and documentation. Supporting subjects in this research were the school principal, deputy principal for curriculum, PAI teachers and educational staff. Research results: First, teachers design creative learning and look for ideas for implementing learning in class. This can be done by using quiziz as a learning medium to improve student learning outcomes in addition to using varied learning videos which are expected to increase interest and motivation to learn. student. Second, implementing Islamic Religious Education Learning Innovations, all Islamic Religious Education teachers make learning videos to attract students' interest during the learning process. Third, Third, in terms of learning outcomes regarding learning innovation, students must achieve the Learning Goal Achievement Criteria (KKTP) with the predicate of having developed and this requires good cooperation between all teachers and school principals.